Reliable Functionalization of 5, 6‐Fused Bicyclic N‐Heterocycles Pyrazolopyrimidines and Imidazopyridazines via Zinc and Magnesium Organometallics. Issue 33 (11th May 2022) - Kumar Rout, Saroj; Kastrati, Agonist; Jangra, Harish; Schwärzer, Kuno; Sunagatullina, Alisa S.; Garny, Maximilien; Lima, Fabio; Brocklehurst, Cara E.; Karaghiosoff, Konstantin; Zipse, Hendrik; Knochel, Paul
Abstract: DFT‐calculations allow prediction of the reactivity of uncommon N‐heterocyclic scaffolds of pyrazolo[1, 5‐ a ]pyrimidines and imidazo[1, 2‐ b ]pyridazines and considerably facilitate their functionalization. The derivatization of these N‐heterocycles was realized using Grignard reagents for nucleophilic additions to 5‐chloropyrazolo[1, 5‐ a ]pyrimidines and TMP2 Zn ⋅  2 MgCl2  ⋅  2 LiCl allowed regioselective zincations. In the case of 6‐chloroimidazo[1, 2‐ b ]pyridazine, bases such as TMP2 Zn ⋅  MgCl2  ⋅  2 LiCl, in the presence or absence of BF3  ⋅  OEt2, led to regioselective metalations at positions 3 or 8. Subsequent functionalizations were achieved with TMPMgCl ⋅  LiCl, producing various polysubstituted derivatives (up to penta‐substitution). X‐ray analysis confirmed the regioselectivity for key functional heterocycles. Abstract : N‐heterocycles, pyrazolopyrimidines and imidazopyridazines were reliably functionalized with the support of DFT ‐ calculations using Grignard reagents as nucleophilic partners and TMPZn‐mediated zincations for 5‐chloropyrazolo[1, 5‐ a ]pyrimidine. Successive regioselective magnesiations with TMPMgCl⋅ LiCl or TMP2 Zn⋅ MgCl2  ⋅  2 LiCl in the presence or absence of BF3  ⋅  OEt2 for the 6‐chloroimidazo[1, 2‐ b ]pyridazine scaffold provided a range of highly functionalized new N‐heterocycles of pharmaceutical interest.